METHYL GREEN : III. REACTION WITH DESOXYRIBONUCLEIC ACID, STOICHIOMETRY, AND BEHAVIOR OF THE REACTION PRODUCT - Kurnick, N. B. (The Rockefeller University Press, 1950)
1. Methyl green ("ethyl green") C. I. Number 685 was examined and found to behave identically with methyl green C. I. Number 684 (no longer available) in respect to molar extinction coefficient, effect of combination with polymerized DNA, failure to react with depolymerized DNA, and effect of pH. 2. The mass law permits the calculation of P/dye. This is found to be 13 P/dye. The same value is obtained when an excess of methyl green is caused to fade by adjusting the pH to 7.5. 3. The compound formed by methyl green with DNA has the same maximum absorption at 642.5 to 645 mµ in the pH range 3.5–7.8, whereas the free dye fades markedly above pH 5.0.